Fragments of Extracellular Matrix as Mediators of Inflammation - Adair-Kirk, Tracy L. (2007)
Classically, the extracellular matrix (ECM) was viewed as a supporting structure for stabilizing the location of cells in tissues and for preserving the architecture of tissues. This conception has changed dramatically over the past few decades with discoveries that ECM has profound influences on the structure, viability, and functions of cells. Much of the data supporting this new paradigm has been obtained from studies of normal and pathological structural cells such as fibroblasts, smooth muscle cells, and malignant cells, as, for example, breast cancer epithelial cells. However, there has also been recognition that effects of ECM on cells extend to inflammatory cells. In this context, attention has been drawn to fragments of ECM components. In this review, we present information supporting the concept that proteolytic fragments of ECM affect multiple functions and properties of inflammatory and immune cells. Our focus is particularly upon neutrophils, monocytes, and macrophages and fragments derived from collagens, elastin, and laminins. Hyaluronan fragments, although they are not products of proteolysis, are also discussed, as they are a notable example of ECM fragments that exhibit important effects on inflammatory cells. Further, we summarize some exciting recent developments in this field as a result of mouse models in which defined ECM fragments and their receptors are clearly implicated in inflammation in vivo. Thus, this review underscores the idea that proteolysis of ECM may well have implications that go beyond modifying the structural environment of cells and tissues.